Predicting Adverse Outcomes in Monochorionic-Diamniotic Twins: The Role of Intertwin Discrepancy in Middle Cerebral Artery Doppler Measurements and the Cerebroplacental Ratio - Mok, Thalia; Afshar, Yalda; Platt, Lawrence D.; Guo, Rong; Rao, Rashmi R.; Pluym, Ilina D.; Silverman, Neil S.; Han, Christina S. (American Journal of Perinatology, 2021)
Objective This study was aimed to evaluate the role of intertwin discrepancy in middle cerebral artery peak systolic velocity (MCA-PSV) and cerebroplacental ratio (CPR) for the prediction of adverse outcomes in monochorionic-diamniotic (MCDA) twin pregnancies.Study Design A retrospective cohort study of MCDA pregnancies that underwent ultrasound surveillance at a perinatal referral center from 2007 to 2017. Intertwin MCA-PSV discrepancy (MCA-ΔPSV-MoM) was defined as the absolute difference of MCA-PSV multiple of the median (MoM) for gestational age between twins. Intertwin CPR discrepancy (CPR-Δ) was defined as the absolute difference of CPR between twins. The maximum MCA-ΔPSV-MoM and CPR-Δ before and after 26 weeks of gestation were assessed as predictors of pregnancy and neonatal outcomes through simple logistic regression models and Pearson's correlation coefficients. Receiver operating characteristic (ROC) curves were generated to determine the predictive value of maximum MCA-ΔPSV-MoM and CPR-Δ.Results A total of 143 MCDA pregnancies met inclusion criteria. There was a significant association between MCA-ΔPSV-MoM at <26 weeks and the development of twin anemia-polycythemia sequence (TAPS; p = 0.007), intrauterine fetal demise (IUFD; p = 0.009), and neonatal intensive care unit (NICU) admission (p < 0.05). MCA-ΔPSV-MoM at ≥26 weeks was associated with the development of TAPS (p < 0.001). CPR-Δ at <26 weeks was associated with the development of twin-twin transfusion syndrome (TTTS; p = 0.03) and NICU admission (p = 0.02). MCA-ΔPSV-MoM at ≥26 weeks was highly predictive of TAPS (area under curve [AUC] = 0.92). A cut-off of 0.44 would identify TAPS with 100% sensitivity and 73% specificity.Conclusion In MCDA pregnancies, intertwin MCA and CPR discrepancies are associated with adverse pregnancy and neonatal outcomes, including TAPS, TTTS, IUFD, and NICU admission. Evaluation of intertwin MCA and CPR differences demonstrated the potential for clinical predictive utility in the surveillance of MCDA twin pregnancies.Key Points
Keywords: intertwin discrepancy; monochorionic-diamniotic twins; middle cerebral artery; cerebroplacental ratio; Doppler